Needs analysis of digital learning media to enhance ownership of learning and collaboration skills in biology education students - Anggun Septi Rahayu; Balqis; Sulisetijono (Journal of Advanced Sciences and Mathematics Education, 2025)
Background: The shift toward a student-centered educational paradigm in the 21st century requires the use of effective digital learning media to enhance students’ ownership of learning and collaboration skills. However, challenges such as low learning motivation, limited student engagement, and the underutilization of diverse learning media remain evident in the Plant Physiology course within Biology Education programs. Aims: This study aims to analyze the need for digital learning media that can enhance students’ ownership of learning and collaboration skills in the Plant Physiology course. Methods: This study employed a quantitative descriptive research design involving 42 undergraduate students and 4 lecturers from the Biology Education program. Data were collected through questionnaires, interviews, and document analysis of the Course Syllabus (RPS) and Lesson Plans (SAP). The collected data were analyzed descriptively to evaluate the extent to which existing learning media support ownership of learning and collaboration skills. Results: The findings reveal that PowerPoint is the most dominant learning medium used, with a usage rate of 58.6%, followed by teaching modules at 21.4% and learning videos at 15.7%. The use of academic articles is very limited, with only 4.3% utilization. Students’ ownership of learning is generally categorized as good, with an average score of 78.4%; however, the indicators of goal orientation and self-direction remain relatively low at 69.64%. Collaboration skills demonstrate a positive average score of 84.66%, yet several indicators have not reached optimal levels. Conclusion: The study concludes that learning in the Plant Physiology course still relies heavily on conventional digital media. Although ownership of learning and collaboration skills show positive trends, they are not yet optimal. These findings emphasize the need to develop innovative digital learning media to strengthen students’ ownership of learning and collaboration skills.